Neurofeedback-Oriented Sign Language Learning Website to Improve Numeracy for Deaf Students - Ketut Merta Yudi Ariana; Adrianus I Wayan Ilia Yuda Sukmana; I Kadek Suartama (Jurnal Media dan Teknologi Pendidikan, 2025)
Numeracy learning for deaf students still faces significant challenges, particularly in attention and visual communication. This study aims to analyze and examine the effectiveness of a sign language-based learning website oriented on neurofeedback in improving numeracy skills among deaf students. The research employed the ADDIE development model, involving six deaf students as participants. Data were collected through expert validation questionnaires, user feasibility tests, pretests, and posttests, with instruments including surveys and numeracy tests. Data analysis was conducted using the Wilcoxon Signed-Rank Test to determine differences between pretest and posttest scores. The results indicated a significant increase in posttest scores compared to pretest (Z = -2.214, p = 0.027), confirming the effectiveness of the media. The website was deemed feasible, engaging, and appropriate for deaf students as it integrated visual elements, interactivity, and neurocognitive principles. This learning media not only enhanced numeracy skills but also improved students’ learning focus. The study implies that neurofeedback-based websites can serve as an alternative model for inclusive technology-based learning, providing opportunities to develop adaptive media tailored to diverse learning needs.